Modelling and simulation in business, economics and management - León-Castro, Ernesto; Merigó, Jose M.; Avilés-Ochoa, Ezequiel; Gil-Lafuente, Anna M.; Herrera-Viedma, Enrique (Technological and Economic Development of Economy, 2019)
Modelling and Simulation in Business, Economics and Management. Technological and Economic Development of Economy, 25(4), pp. 571-575.